THE THERMAL REGIME DYNAMICS IN CALLOVIAN-OXFORDIAN SEAS OF NORTHWESTERN EURASIA: IMPLICATIONS OF RELATIVE PALEOTEMPERATURE DATA - Kiselev D.N. (My University, 2004)
Six paleothermal and paleohydrologic settings in Callovian-Oxfordian seas of northwestern Eurasia are modeled for six time intervals corresponding in duration to the substage. The modeling principle is based on the study of probabilistic relationships between various faunal elements from different paleobiogeographic provinces in a single species assemblage, ammonites in the considered case. The method opens a possibility to recognize periods of subglobal and local warming and cooling, to reconstruct currents in the entire sea system, and to specify paleotemperature distribution. Two periods of water mass warming (middle Callovian and middle Oxfordian) and three periods of their relative cooling (early Callovian, Callovian-Oxfordian boundary period, and late Oxfordian) are distinguished in the Callovian-Oxfordian. All paleobasins of northwestern Eurasia (Arctic, Central Russian, European, Peri-Tethyan, Tethyan) had autonomous circulation systems with different paleotemperature characteristics. Because of this, dynamics of the thermal regime in the Callovian-Oxfordian basins primarily reflects variations in the hydrological regime rather than paleoclimatic changes. © 2004 by MAIK.
Keywords: Oxfordian; Callovian; Mesozoic::Jurassic::Upper::Oxfordian; Мезозой::Юрская::Средний::Келловейский; Mesozoic::Jurassic::Middle::Callovian; Мезозой::Юрская::Верхний::Оксфордский